Bioinspired Synthesis of the Central Core of Halichonadin H: The Passerini Reaction in a Hypothetical Biosynthesis of Marine Natural Products - Ichikawa, Yoshiyasu; Yamasaki, Toshiki; Nakanishi, Keisuke; Udagawa, Yutaro; Hosokawa, Seijiro; Masuda, Toshiya (Synthesis, 2019)
A pathway is proposed for the biosynthesis of the unique homodimeric terpene, halichonadin H. The proposed biosynthetic pathway involves two key Passerini reactions of eudesmane-type terpene isocyanides. The Passerini reaction of a model terpene isocyanide and formaldehyde afforded an α-hydroxy acetamide, which was further subjected to oxidation and a second Passerini reaction. This reaction sequence furnished an α-hydroxy malonamide connected with two identical terpene units which is the identical structural motif found in halichonadin H.
Keywords: marine natural products; terpenes; isocyanides; biosynthesis; Passerini reaction